Raman spectroscopy of DNA-wrapped single-walled carbon nanotube films at 295 and 5 K - Karachevtsev, V.A.; Glamazda, A.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Resonance Raman spectra of DNA-wrapped single-walled carbon nanotubes films were studied at 5 and 295 K in the range of radial-breathing (175–320 cm–1) and tangential (1520–1625 cm–1) modes. The spectra were compared with those of nanotubes in bundles. At 5 K in the spectrum of film an upshift of bands regard to their spectrum at high temperature and the intensity redistribution among bands of two samples were observed. The magnitude of this upshift depends on the nanotube type. The influence of temperature lowering, the environment and the electron–phonon coupling on the Raman spectrum of nanotubes are discussed.